2011
DOI: 10.1136/amiajnl-2011-000093
|View full text |Cite
|
Sign up to set email alerts
|

The Yale cTAKES extensions for document classification: architecture and application

Abstract: The F(1)-Score of the system for the retrieval of abdominal radiology reports was 96%, and was 79%, 91%, and 95% for the presence of liver masses, ascites, and varices, respectively. The authors released YTEX as open source, available at http://code.google.com/p/ytex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 23 publications
0
57
0
Order By: Relevance
“…All the text processing and analysis utilized the cTAKES (version 3.0) which stores the analysis results in the UIMA Common Analysis Structure (CAS) [18]. The cTAKES outputs CAS in XML representation.…”
Section: Methodology and Materialsmentioning
confidence: 99%
“…All the text processing and analysis utilized the cTAKES (version 3.0) which stores the analysis results in the UIMA Common Analysis Structure (CAS) [18]. The cTAKES outputs CAS in XML representation.…”
Section: Methodology and Materialsmentioning
confidence: 99%
“…They concluded that more advanced abbreviation recognition modules are necessary. Osborne et al [24] applied MetaMap and YTEX [25], which is an extension of cTAKES to two concept recognition tasks. Their results suggested that YTEX would be a better system for "off the shelf" concept mapping.…”
Section: Diagnostic Knowledge Extraction Using Metamap and Ctakesmentioning
confidence: 99%
“…Fields include temporal, anatomic, and certainty modifiers for each finding (Fig 7), whose values can be obtained from existing terminologies (eg, the UMLS Metathesaurus) and custom-built dictionaries developed for specific tasks. The opensource NLP package cTAKES similarly relies on significant linguistic components (19,20) in conjunction with statistical and machine learning approaches (discussed in the following section).…”
Section: Linguistic Approachmentioning
confidence: 99%